2019
DOI: 10.1177/0164027519886176
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Home Care Worker: Job-Seekers’ Push and Pull Factors

Abstract: This study examined “push and pull” factors associated with the decision to become home care workers among job-seekers in Israel. Participants completed measures of ageism, anxiety about aging, attitudes toward the home care profession, and personal relationship with older adults. Of 1,492 participants, 32.0% accepted the offer to become home care workers and were no longer in the job market, 36.7% accepted the offer but worked in the past, and 31.2% refused the offer. Compared to participants currently employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies identifying issues with homecare provision often neglect to set out precisely what the nature of these problems are (Bragstad et al, 2012 ; Bryan, 2010 ; Hendy et al, 2012 ). Workforce instability is one factor known to affect care supply internationally, with low pay and low status making the care sector an unattractive employer, especially in higher‐income countries (Shinan‐Altman et al, 2020 ; Stone, 2017 ). In England, local authorities have a responsibility to work with local providers to develop a shared understanding of current and future social care needs and ensure these can be met (Local Government Association, 2018 ), but the stakeholders we spoke to identified mismatched supply and demand linked to problems recruiting and retaining care workers in the places and at the times they were required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies identifying issues with homecare provision often neglect to set out precisely what the nature of these problems are (Bragstad et al, 2012 ; Bryan, 2010 ; Hendy et al, 2012 ). Workforce instability is one factor known to affect care supply internationally, with low pay and low status making the care sector an unattractive employer, especially in higher‐income countries (Shinan‐Altman et al, 2020 ; Stone, 2017 ). In England, local authorities have a responsibility to work with local providers to develop a shared understanding of current and future social care needs and ensure these can be met (Local Government Association, 2018 ), but the stakeholders we spoke to identified mismatched supply and demand linked to problems recruiting and retaining care workers in the places and at the times they were required.…”
Section: Discussionmentioning
confidence: 99%
“…It also is important to acknowledge the fact that in the present study care was provided to older people. Thus, stereotypes of older people might play a role in the wish to perform the job (Shinan-Altman et al ., 2020) and eventually return to one's home country. Viewing older care recipients as ‘old bags’, as mentioned by the least educated respondent, certainly does not add much appeal to the job and might make the emotional work even harder (Hochschild, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Shimizu [10] found that the more familiar caregivers are with older people, the more ageism they have. In fact, it has been reported that those who want to care for older people are more ageist [13]. While care workers in Japan may be familiar with older people, they need to learn if they have ageism and, if so, how it can compromise older people's health.…”
Section: Discussionmentioning
confidence: 99%